2023
DOI: 10.3390/ijms24010781
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Atopic Dermatitis: Focus on Interleukins as Disease Drivers and Therapeutic Targets for Novel Treatments

Abstract: Atopic dermatitis is a chronic, recurrent inflammatory skin disorder manifesting by eczematous lesions and intense pruritus. Atopic dermatitis develops primarily as a result of an epidermal barrier defect and immunological imbalance. Advances in understanding these pathogenetic hallmarks, and particularly the complex role of interleukins as atopic dermatitis drivers, resulted in achieving significant therapeutic breakthroughs. Novel medications involve monoclonal antibodies specifically blocking the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 168 publications
0
10
0
Order By: Relevance
“…Our study also showed that patients with AD were less likely to have hypertension and DM, although other studies found a positive correlation between AD and MetS 16,17,22,26 . The cytokines released in AD, including interleukin (IL)-17 and IL-22, both of which play a role in the chronic phase of AD 51 , were suggested to increase cardiovascular risks [52][53][54] , with their chronic in ammatory effects increasing the risk of MetS in AD patients 25,55,56 . The con icting results obtained in our study vs. previous studies may re ect different genetic, socioeconomic, nutritional, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that patients with AD were less likely to have hypertension and DM, although other studies found a positive correlation between AD and MetS 16,17,22,26 . The cytokines released in AD, including interleukin (IL)-17 and IL-22, both of which play a role in the chronic phase of AD 51 , were suggested to increase cardiovascular risks [52][53][54] , with their chronic in ammatory effects increasing the risk of MetS in AD patients 25,55,56 . The con icting results obtained in our study vs. previous studies may re ect different genetic, socioeconomic, nutritional, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Th2 and Th22 immune responses are believed to be chiefly activated during the acute phase of AD, with a comparatively reduced induction of Th17 markers. Patients with chronic AD exhibit an amplified Th1 response in addition to upregulated Th2 and Th22 responses [ 30 32 ] (Fig. 1 ).…”
Section: Immune and Inflammatory Mechanism Of Atopic Dermatitismentioning
confidence: 99%
“…247 A variety of mediators, including IL-4, IL-13, IL-31, and TSLP, bind specific transmembrane receptors and stimulate the JAK-STAT pathway, thereby initiating intracellular signaling and exerting proinflammatory effects in AD. 248,249 In-depth explorations of AD pathogenesis have suggested that the JAK-STAT pathway is involved in Th2 immune polarization, eosinophil activation, and skin barrier destruction during AD progression. 250 A greater understanding of the roles of the JAK-STAT pathway in AD has enabled the application of JAK inhibitors as a new approach to AD treatment.…”
Section: The Jak-stat Pathway and Diseasesmentioning
confidence: 99%